2018
DOI: 10.1007/s00059-018-4702-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of novel biomarkers for heart failure

Abstract: The overall diagnostic accuracy of copeptin, galectin-3, hs-cTnT, MR-proANP, and ST2 was relatively good. MR-proADM had a poor capacity to confirm or exclude HF. Improving the diagnostic accuracy of HF by a combination of biomarkers could be considered in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Although the usefulness of Gal‐3 as a biomarker of heart disease has gained support from the findings of many clinical studies, more recent studies have revealed inconsistency, questioning the usefulness of Gal‐3 in predicting MACE, even though higher blood levels of Gal‐3 are consistent findings in almost all reports (Abou Ezzeddine et al, ; Arangalage et al, ; Begg et al, ; Besler et al, ; de Boer et al, ; Huang et al, ; Jansen et al, ; Lopez et al, ; Stoltze Gaborit et al, ). For instance, in studies on community cohorts or HF patients, multiple biomarkers were employed and compared for individual prognostic power and Gal‐3 was found to have insignificant clinical value (Bayes‐Genis et al, ; de Boer et al, ).…”
Section: Gal‐3 As a Biomarker Of Heart Disease: Influence Of β‐Adrenomentioning
confidence: 99%
“…Although the usefulness of Gal‐3 as a biomarker of heart disease has gained support from the findings of many clinical studies, more recent studies have revealed inconsistency, questioning the usefulness of Gal‐3 in predicting MACE, even though higher blood levels of Gal‐3 are consistent findings in almost all reports (Abou Ezzeddine et al, ; Arangalage et al, ; Begg et al, ; Besler et al, ; de Boer et al, ; Huang et al, ; Jansen et al, ; Lopez et al, ; Stoltze Gaborit et al, ). For instance, in studies on community cohorts or HF patients, multiple biomarkers were employed and compared for individual prognostic power and Gal‐3 was found to have insignificant clinical value (Bayes‐Genis et al, ; de Boer et al, ).…”
Section: Gal‐3 As a Biomarker Of Heart Disease: Influence Of β‐Adrenomentioning
confidence: 99%
“…Newer biomarkers, such as mid regional pro-adrenomedullin (MR-proADM) and sST2 hold significant potential for prediction and diagnosis of HF, and may augment the use of NP measurement [ 7 , 18 , 53 , 54 ]. MR-proADM and sST2 production are influenced, in part, by the hemodynamics of a fluid-overloaded state in HF, including endothelial shear stress [ 55 ], myocyte strain [ 56 , 57 ] and alveolar strain in pulmonary edema [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Vazquez-Montes MDLA et al (2020) [85] reported that MR-proADM was not superior to NT-proBNP in the prediction of chronic HF. In a recently published meta-analysis comparing the diagnostic value of novel biomarkers for HF, Huang Z. et al (2020) [86] revealed that MR-proADM had a poor discriminative value to confirm or exclude HF. Whether a serial measurement of MR-proADM is able to reclassify a risk of death due to HF individually depending on the presence of other CV risk factors including T2DM is not yet fully understood, because no correlation between T2DM and levels of MR-proADM has been found for mortality or HF hospitalization [87].…”
Section: Adrenomedullinmentioning
confidence: 99%